2013
DOI: 10.1007/978-3-642-16712-6
|View full text |Cite
|
Sign up to set email alerts
|

Encyclopedia of Biophysics

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher nor EBSA can accept any legal responsibility for any errors or omiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…∂s 2 is the tangent vector along the chain [101][102][103]. To straighten out the chain, work needs to be done against the bending energy ( Figure 15).…”
Section: The Worm-like Chain Modelmentioning
confidence: 99%
“…∂s 2 is the tangent vector along the chain [101][102][103]. To straighten out the chain, work needs to be done against the bending energy ( Figure 15).…”
Section: The Worm-like Chain Modelmentioning
confidence: 99%
“…The replication clamps are ring-shaped complexes that encircle dsDNA and slide freely on the duplex, conferring processivity to their respective replicative DNA polymerase ( Kunkel and Burgers, 2014 ; Kunkel and Burgers, 2017 ; Nick McElhinny et al, 2008 ; ODonnell and Kurth, 2013 ; Pursell et al, 2007 ; Yao and O’Donnell, 2021 ). In eukaryotes, PCNA (Proliferating Cell Nuclear Antigen) functions with replicative polymerases Pol δ on the lagging strand and Pol ε on the leading stand ( Kunkel and Burgers, 2014 ; Kunkel and Burgers, 2017 ; Nick McElhinny et al, 2008 ; ODonnell and Kurth, 2013 ; Pursell et al, 2007 ; Yao and O’Donnell, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The replication clamps are ring-shaped complexes that encircle dsDNA and slide freely on the duplex, conferring processivity to their respective replicative DNA polymerase ( Kunkel and Burgers, 2014 ; Kunkel and Burgers, 2017 ; Nick McElhinny et al, 2008 ; ODonnell and Kurth, 2013 ; Pursell et al, 2007 ; Yao and O’Donnell, 2021 ). In eukaryotes, PCNA (Proliferating Cell Nuclear Antigen) functions with replicative polymerases Pol δ on the lagging strand and Pol ε on the leading stand ( Kunkel and Burgers, 2014 ; Kunkel and Burgers, 2017 ; Nick McElhinny et al, 2008 ; ODonnell and Kurth, 2013 ; Pursell et al, 2007 ; Yao and O’Donnell, 2021 ). Structural studies showed that, the E. coli β-clamp is a homodimer, while the T4 phage clamp and archaeal and eukaryotic PCNA clamps are homotrimers, all of which display six domains having similar chain folds and remarkable pseudo sixfold symmetric architecture with an obvious ancestor in evolution ( Gulbis et al, 1996 ; Kong et al, 1992 ; Krishna et al, 1994 ; Matsumiya et al, 2001 ; Yao and O’Donnell, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also of interest is the ultra-short emission wavelength at 215 nm which clearly sits at a wavelength substantially shorter than what can be achieved using the ultimate challenger heterostructure based on a gallium plane embedded into AlN barrier layers (235 nm at 8 K) [32]. Although a lot of efforts are at the time being focused towards the 260-270 nm range [33,34] where light absorption by DNA molecules is important, hBN-related devices will be of paramount importance for fully covering the 200-300 nm range for nucleic acids (DNA and RNA) where the UV absorbance is due to transitions of the planar purine and pyrimidine bases (see Figure 1 where the wavelengths that can be attributed to GaN-AlN devices are yellowed while the region of hBN-related ones is greyed) [35]. The detailed analysis of light-matter interaction for DNA in the 200 nm range when the system is photo-perturbed (like for instance under a dense photoexitation) is living its infancy.…”
Section: The Early Daysmentioning
confidence: 99%
“…UV spectra of the DNA nucleotides (This figure is partly plotted from data published reference[35]). …”
mentioning
confidence: 99%